A new integrated heat pump option for heat upgrading in Cu-Cl cycle for hydrogen production. (2nd November 2017) - Almahdi, M.; Dincer, I.; Rosen, M.A.
Highlights: Heat pump is proposed for heat upgrading in Cu-Cl cycle for hydrogen production. Heat pumps performance is evaluated energetically and exergetically. The system base case energetic and exergetic COPs of 1.76 and 1.15, respectively. The majority of exergy destruction occurs in the decomposition reactor (45%). Abstract: A potential cascaded vapor compression heat pump is proposed to address the high temperature heat demand in the copper chlorine (Cu-Cl) thermochemical cycle for hydrogen production. The configuration studied is a cuprous chloride CuCl vapor compression heat pump cascaded with a biphenyl (C6 H5 )2 heat pump. Such cascaded heat pumps is meant to upgrade heat from nuclear power plants with a heat input temperature of approximately 300 °C or industrial waste heat to meet the Cu2 OCl2 decomposition reactor heat demand. Energy and exergy analyses are performed to understand the performance of the heat pump. It is determined that the CuCl-biphenyl heat pump exhibits a high coefficient of performance for certain operating conditions relating to the compressor isentropic efficiency and the excess CuCl feed temperature. The base energetic and exergetic coefficient of performances of the CuCl-biphenyl heat pump are 1.76 and 1.15 respectively.